Pediculus humanus capitis infestation in childhood and adolescence: strategies for prevention and control (Research, Society and Development, 2022)
Introduction: Pediculus humanus capitis is a pathological condition characterized by the presence of blood-sucking ectoparasites commonly known as "sucking lice". Lice infestation is not only common in underdeveloped or developing countries, but a type of problem that affects everyone. Methodology: This is an integrative literature review. The search took place in the Virtual Health Library, where it was possible to find 73 articles. The final sample consisted of seven articles. The articles were analyzed using Bardin's theory and organized on the Rayyan platform, where they were analyzed with blindness by two researchers. Results: A study implemented a program for the elimination of lice with a strategy for long-term follow-up, with training for health professionals regarding the fight against capillary pediculosis. An inspection was carried out on the children's hair, in addition to spreading informative posters about the prevention of lice throughout the city. Over time, parents or guardians understood the role in preventing and caring for children's hair, so head inspections were discontinued. Final considerations: There are some policies that aim to combat this problem and some of them fight for the end of the exclusion of children from classes because it is infested and defend that prevention is the best way to overcome the problem.